The Tlingit - Osinski, Alice (Chicago : Childrens Press, 1990)
Describes the traditional lifestyle, arts and crafts, changing land, and modern life of the Tlingit Indians.
Includes index.
3.9
K-3
Keywords: Tlingit Indians -- Juvenile literature; Tlingit Indians; Indigenous people of North America -- Juvenile fiction; Tlingit Indians; Native Americans; Native Americans -- North America; Native Americans -- United States; Tlingit Indians; Indigenous people of North America -- Juvenile fiction